Some aspects of morphometry, systematics and biogeography of the freshwater turtles, Pangshura (testudines: Geoemydidae) of Pakistan - Safi, Amtyaz; Zaheer Khan, Muhammad; Usman Ali Hashmi, Muhammad; Kanwal, Roohi; Karl, Hans-Volker (SPC Journal of Environmental Sciences, 2020)
The present paper based on multivariate morpho-metry, systematics and biogeographically analyses of the hard-shell freshwater turtles of genus Pangshura found in Pakistan. Allo-metric changes in the size of body were examined in the live collected specimens. The morpho-metric measurements and comparative study of Pangshura clearly revealed sexual di-morphism and both the sexes can easily be differentiated. Females are larger in size than males in of this texon. The present study revealed that P. tecta are less common in distribution than P. smithii in in the studied area of Pakistan. The current study presents a morpho-metric relationship between extant and extinct species of Pangshura taxon for the first time. A holotype of this taxon, Pangshura tatrotia is described here, which is also considered a sister to P. tecta and a fifth species so far of this texon.